UIN Mahmud Yunus Batusangkar Economic Empowerment Step For Kumanis Village - Sumiki Kamel (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
It takes ability and insight to address the different issues that the community faces when constructing a village or nagari. There is no ivory that is uncracked. This indicates that despite my frailty as the Guardian of the Nagari Kumanis, Sijunjung Regency, West Sumatra, a powerful force is guiding me as I work with the Nagari Kumanis populace. UIN Mahmud Yunus Batusangkar is the group. The university and LPPM have always collaborated to advance Nagari Kumanis ever since it was known as STAIN Batusangkar, then changed to IAIN Batusangkar, and is currently known as UIN Mahmud Yunus Batusangkar. The five keys service initiatives for LPPM UIN Mahmud Yunus Batusangkar in Nagari Kumanis include management of BUMNAG and UMKN, promotion of traditional Nagari institutions, increasing religiosity through monthly wirids, and educational growth through parental activities. UMKN is supported and managed by Featured Program for Service to LPPM UIN Mahmud Yunus Batusangkar through BUMDES Batu Jonggi Kumanis. Central BRI and Pajajaran University have ranked BUMDES Batu Jonggi as the 16th best village in the country as a consequence of its intensive and persistent coaching. We, the Nagari Kumanis, would want to convey our sincere appreciation to LPPM UIN Mahmud Yunus Batusangkar.